SPORTS MARKETING TOOLS FOR ENTERPRISE PROMOTION ON THE MARKET (ON THE EXAMPLE OF POLAND) - VASILIEVA, Valentina; BUHAIENKO, Tetiana; LIANNOI, Mykhailo; CHERNIAKOVA, Zhanna; VORONA, Vita (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article analyses marketing tools that are expedient to use in modern conditions for the purpose of promoting on the enterprise market in the field of physical culture and sports services (on the example of Poland). It has been proven that sports marketing has a certain number of common features with the marketing of other types of services. Therefore, while promoting an enterprise in the field of physical culture and sports services on the market, we can use marketing tools for the promotion of other enterprises in the service sector. It has been found out that sponsorship is an important tool for the promotion of an enterprise in the field of physical culture and sports services on the market. The characteristics to the main forms of sports sponsorship have been given. The main reasons for the growing importance of sponsorship as a form of promotion are distinguished. The article highlights the objectives of sponsorship which are divided into four categories (creating the image of the company, company, customers, local community). The detailed characteristics of each category have been presented. The article examines that the types of sponsorship can be classified according to several characteristics according to the sponsoring organizations, the number of sponsors and the nature of sponsored services. Special attention has been paid to a peculiar type of sponsorship such as license sponsorship, which consists in the agreement to use the name, emblem, symbol, trademark or official or decorative picture of the sponsor. The article proves this type of sponsorship using the polish experience. In the context of the research, it is important to observe marketing rights when studying the role of marketing in the promotion of an enterprise in the field of physical culture and sports services on the market. Marketing rights include those used both on-site and during the event, as well as exercised in the period between separate events. It is stressed that you can distinguish between the rights to sell your own products with a sponsored visual identity or to promote and sell the sponsor’s products and services directly during sponsored events or in the rights holder’s communication channels. Focus on the Polish experience the key principles which help to involve a powerful person into marketing activities should be considered. Each defined principle is proved by the Polish example.